2016
DOI: 10.1515/bog-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the geography of tourism innovation in Western Cape Province, South Africa

Abstract: Abstract. This paper interrogates the geography of tourism innovation in the Western Cape, South Africa. In particular, innovations by tourism firms are mapped and local tourism innovation networks are analysed. Networking behaviour is examined since it is regarded as indispensable for accessing knowledge and learning for innovation purposes. The analysis draws on a broader investigation of tourism innovation and networking within the Western Cape province. It is revealed that the main tourist regions in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
2
22
0
2
Order By: Relevance
“…It was confirmed that the main tourism regions seem to be more innovative than peripheral areas. This corresponds with the finding that more urbanized places are often where larger (and thus more innovative) companies are located (Booyens & Rogerson, 2016). This is in line with the effects of agglomeration on urban economies (Booyens & Rogerson, 2016;Cooke & de Propris, 2011).…”
Section: Geography Of Innovation In Tourism Companiessupporting
confidence: 87%
See 2 more Smart Citations
“…It was confirmed that the main tourism regions seem to be more innovative than peripheral areas. This corresponds with the finding that more urbanized places are often where larger (and thus more innovative) companies are located (Booyens & Rogerson, 2016). This is in line with the effects of agglomeration on urban economies (Booyens & Rogerson, 2016;Cooke & de Propris, 2011).…”
Section: Geography Of Innovation In Tourism Companiessupporting
confidence: 87%
“…This corresponds with the finding that more urbanized places are often where larger (and thus more innovative) companies are located (Booyens & Rogerson, ). This is in line with the effects of agglomeration on urban economies (Booyens & Rogerson, ; Cooke & de Propris, ). However, the tourism industry in rural areas often has significant impact on innovative local development (Brouder, ).…”
Section: Theory and Hypothesessupporting
confidence: 82%
See 1 more Smart Citation
“…Distinguishing between these various innovation types in practice is challenging as innovations are often bundled together, particularly in the tourism industry (Booyens & Rogerson, ): Innovation in one area requires or leads to subsequent innovations in others (Barras, ). Therefore, this paper follows the classification by Hjalager (), who has elaborated how to adapt the existing innovation typologies discussed above specifically for investigating innovation types within the tourism industry: product, process, managerial, marketing, and institutional innovations (Table ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…in that placing tourists in the centre of the initial development stage of products and tourism markets in the final stage of this process, aiming to increase exportation earnings (Blasco, Guia & Prats, 2014;Bohlin, Brandt & Elbe, 2016). To Booyens and Rogerson (2016), it is also necessary to combine local and non-local, tangible and intangible resources, such as: knowledge (tacit, technical and scientific), technology, professional experience and other personal and professional skills, fundamental for the innovation of products and services. Offering a tourism experience relies on a type of creative tourism that sets innovation at the centre of product development, thus responding to changing demand motivations.…”
Section: Literature Reviewmentioning
confidence: 99%